African migration and the novel exploring race, civil war, and environmental destruction - Taylor, Jack 1982- (Rochester studies in African history and the diaspora, 2024)
Examines how current novels dealing with African migration address social issues, immigrant subjectivity, and the politics of migration. African Migration and the Novel: Exploring Race, Civil War, and Environmental Destruction explores pressing social and political issues such as racial identity, environmental devastation, human trafficking, and political violence through the lens of novels of African migration. The book details how authors such as Chika Unigwe, Chris Abani, Dinaw Mengestu, In Koli Jean Bofane, Boubacar Boris Diop, and others develop "the migratory imagination": the creative means mobilized within their novels to expose the reader to contemporary social issues. Drawing on and synthesizing a multitude of theoretical frameworks including ecocriticism, postcolonial theory, genre studies, Black studies, paratextual reading, and political economy, the book argues for the flexibility of the migration novel as a genre. African Migration and the Novel traces migratory routes such as Nigeria to London and Belgium, Congo to Paris, Ethiopia to Washington, DC, and internal migration resulting from environmental destruction in Sierra Leone, while paying deep attention to the historical and political conditions described in the novels. The subjectivities and livelihoods of immigrants, refugees, those living in exile, and asylum seekers are all represented in the migration novels under discussion. Ultimately, this work demonstrates the promise of the African migration novel to awaken a sense of justice in the reader